2002
DOI: 10.1046/j.1526-0968.2002.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Dextran Sulfate Cellulose Beads for Whole Blood Infusion Low‐Density Lipoprotein‐Hemoperfusion

Abstract: We describe results from a feasibility study of a newly developed low‐density lipoprotein (LDL) adsorbent designed for use in whole‐blood infusion LDL‐hemoperfusion. The adsorbent has almost the same chemical structure as the Liposorber adsorbent (dextran sulfate cellulose beads) but has a larger particle size. In whole‐blood perfusion tests, the adsorbent adsorbed atherogenic LDL cholesterol directly from whole blood but left concentrations of high‐density lipoprotein cholesterol largely unchanged. In whole‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 21 publications
2
12
1
Order By: Relevance
“…Kobayashi et al found that C3a was reduced during a single pass through an LDL adsorbent column ex vivo whereas C5a was unchanged [17]. This is apparently in contrast to our findings, as we observed a marked increase in C3a with all columns.…”
Section: Complementcontrasting
confidence: 99%
See 1 more Smart Citation
“…Kobayashi et al found that C3a was reduced during a single pass through an LDL adsorbent column ex vivo whereas C5a was unchanged [17]. This is apparently in contrast to our findings, as we observed a marked increase in C3a with all columns.…”
Section: Complementcontrasting
confidence: 99%
“…This column utilizes dextran sulphate cellulose beads for adsorption of LDL. It is modified with regard to the particle size and allows for perfusion and adsorption of LDL cholesterol directly from whole blood [17,18].…”
Section: Ldl Apheresismentioning
confidence: 99%
“…The affinity ligand, dextran sulfate, has been found to exhibit a high affinity to LDL and a low toxicity [18]. The dextran sulfate whole blood adsorber is a new LDL apheresis system, which has been recently introduced [16,17,19]. The dextran sulfate plasma adsorption system uses two LDL adsorption columns with negatively charged dextran sulfate cellulose beads to selectively remove positively charged apo B containing lipoproteins, such as very low-density lipoprotein (VLDL), low-density lipoprotein (LDL), or lipoprotein (a), from plasma.…”
Section: Introductionmentioning
confidence: 99%
“…It is modified with regard to the particle size and allows for perfusion and adsorption of LDL cholesterol directly from whole blood [20][21][22].…”
Section: Ldl Apheresismentioning
confidence: 99%